2017
DOI: 10.1088/1742-6596/896/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microstructure on the sheared edge quality and hole expansion ratio of hot-rolled 700 MPa steel

Abstract: Abstract. The effects of microstructure on the cutting and hole expansion properties of three thermomechanically rolled steels have been investigated. The yield strength of the studied 3 mm thick strip steels was approximately 700 MPa. Detailed microstructural studies using laser scanning confocal microscopy (LCSM), FESEM and FESEM-EBSD revealed that the three investigated materials consist of 1) single-phase polygonal ferrite, 2) polygonal ferrite with precipitates and 3) granular bainite. The quality of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thus, the formation of granular bainite should be avoided in order to achieve better HER. Two recent studies [34,35] reported that large precipitates such as micrometric TiN or cementite can act as the primary source of void nucleation in complex phase steels, which deteriorates HER. Large TiN are also known to deteriorate the toughness [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the formation of granular bainite should be avoided in order to achieve better HER. Two recent studies [34,35] reported that large precipitates such as micrometric TiN or cementite can act as the primary source of void nucleation in complex phase steels, which deteriorates HER. Large TiN are also known to deteriorate the toughness [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to punch shape and hole edge condition, microstructure of the material is also known to have effects on the hole expansion. For example, high hardness difference between ferrite and martensite phases [6] and secondary constituents, such as inclusions and cementite [7], have been reported to decrease HER results.…”
Section: Introductionmentioning
confidence: 99%